The Use of Nanomaterials for Road Construction - Imoni, Samson; Tiza, Michael Toryila; Onyebuchi, Mogbo; Akande, Ebenezer Ogirima (Bincang Sains dan Teknologi, 2023)
The integration of nanotechnology into the construction industry, specifically in developing asphalt and concrete pavement materials, holds great promise for enhancing infrastructure performance and durability. Nanomaterials, characterised by their nanoscale dimensions, typically less than 100 nanometers, are increasingly employed in pavement construction. This abstract provides an overview of various nanomaterials and their potential impact on road construction. Nanomaterials like nano-silica, nano clay, carbon nanotubes, nanocarbon black, nanofibers, nano titanium dioxide, nano alumina, and nano zinc oxide are explored in this context. These materials offer unique properties due to their small size and high surface area. For instance, nano silica has demonstrated its ability to enhance stiffness, strength, longevity, and resistance to rutting and cracking in asphalt pavement. Nanoclay reinforces mechanical and thermal properties in asphalt and concrete, improving overall performance. Carbon nanotubes and graphene show promise in concrete pavement by enhancing mechanical properties and reducing cracking. Furthermore, nanocoatings are being explored for pavement surfaces, offering benefits such as improved slip resistance, reduced noise, increased durability, and pollution resistance. Despite the potential advantages, challenges exist, including the need for standardised testing and characterisation procedures and the initial cost of incorporating nanoparticles into pavement materials. Ongoing research and development efforts are focused on addressing challenges and making these innovations more practical and cost-effective for widespread implementation. Nanomaterials have emerged as a viable solution to improve road construction, offering benefits for infrastructure performance while minimising environmental impact.